Structure–activity relationships of some hederagenin diglycosides: Haemolysis, cytotoxicity and apoptosis induction - Chwalek, Martin; Lalun, Nathalie; Bobichon, Hélène; Plé, Karen; Voutquenne-Nazabadioko, Laurence (Biochimica et biophysica acta, 2006)
Hederagenin saponins are largely represented in nature and possess many biological activities such as haemolytic, antiviral, fungicidal, molluscicidal or cytotoxic, partially due to their interaction with the cell membrane. The lysis of erythrocytes (haemolysis) is a simple test to evaluate this adsorption, and this activity has been linked to the structure of the aglycone and also depends on the sugar moiety of the saponin. To further complete our study of the structure–activity relationships of triterpenoid saponins, α-hederin and related hederagenin diglycosides were synthesized to better understand the influence of the second sugar (α- l-rhamnose, β- d-xylose or β- d-glucose) and the substitution of this sugar on α- l-arabinose (position 2, 3 or 4). Haemolysis and cytotoxic activity on KB cells were tested. These compounds probably interact with membrane cholesterol and produce destabilization of the membrane inducing haemolysis. Cytotoxicity could involve the same mechanism, although some saponins induce an apoptotic process. The nuclear structure of the KB cell was thus investigated by confocal microscopy. The cytotoxic activity of a second group of hederagenin glucoside saponins was also evaluated. Our results showed that cytotoxicity was a result of both the sugar part and the structure of genin (carboxylic acid or methyl ester).